Quality Evaluation of Immersive Virtual Reality Interactive Art Design under Cultural Heritage Digitization under Interval Valued Neutrosophic Numbers - Xing She; Ying Liu; Qian Liu; Le Zhang (Neutrosophic Sets and Systems)
The integration of disciplines has become a crucial issue that the entire society must deal with due to the economy's and society's rapid development. Particularly for teaching art and design, the new features of quickly iterative technology and the developing theory of the digital age presented new difficulties. Simultaneously, as computer hardware continues to advance, new simulation technologies are continually emerging, opening new avenues for creative design work. As a methodical endeavor, teaching art design should incorporate cutting-edge instructional strategies with scientific theories. This study proposes a multi-criteria decision-making (MCDM) approach to evaluate the immersive virtual reality interactive art design under cultural heritage digitization. This study uses two MCDM methods such as the CRITIC method to compute the criteria weights and the ARAS method to rank the alternatives. Two MCDMs are used under the interval-valued neutrosophic sets (IVNSs) to deal with vague and uncertain information. We collect ten criteria and five alternatives to be evaluated by four experts. The sensitivity analysis is conducted to show the stability of the rank under different cases.